Searching for the fundamentals of rehydroxylation dating of archaeological ceramics via NMR and IR microscopy. Issue 10 (10th March 2021) - Avramovska, Marija; Chmelik, Christian; Derkowski, Arkadiusz; Fantalkin, Alexander; Freude, Dieter; Haase, Jürgen; Hare, Vincent; Kärger, Jörg; Kuligiewicz, Artur; Moinester, Murray
Abstract: Determining absolute ages of archaeological ceramics is crucial for understanding past societies and reconstructing their accurate chronologies. The amount of OH hydroxyl chemically combined with ceramic material has been claimed to provide an 'internal clock' that can be read via RHX dating to determine the elapsed time since it was fired. The hydroxylation reaction, controlled by the slow diffusion of water molecules within the structure of clay minerals, has been described by a quartic root (time) 1/4 power law dependence. However, previous attempts of RHX dating by gravimetric methods have not been successful, since the mass gain due to OH hydroxylation or H2 O hydration could not be distinguished. We carried out a preliminary study of RHX dating via Infrared (IR) and Nuclear Magnetic Resonance (NMR) spectroscopy of three pure clay minerals, beidellite, illite and muscovite, as analogues for components of archaeological materials. Our study of RHX kinetics via IR microscopy gives important evidence regarding the quartic root time power law dependence. Furthermore, NMR allows us to study the structural as well as dynamic features of clays. Through observing the H/D exchange, we obtain access to the relevant activation energies and diffusion coefficients. We show that IR and NMR methods hold significant potential to refine the RHX dating method by understanding the elementary processes of mass transfer and hydroxylation in pure clays.